Efforts to Improve Under the Ball Service Ability of Volleyball With Modified Plastic Balls - Leonardo Oktovianus Tanasale; Andi Syaiful; Heppy Hein Wainggai (Tinta Emas Publisher, 2023)
This study aims to improve the ability to serve down in volleyball games using modified plastic balls for fifth grade students of SD Negeri Inpres Pasir 2. This research uses the Classroom Action Research (PTK) method by involving students as participants in the learning process. The research was conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection. The modification made in this study is the use of plastic balls as a tool for lower service training, replacing ordinary volleyballs. Data collection uses observation, tests, and questionnaires. The data analysis technique in this study uses quantitative descriptive. The results showed that in cycle 1, 63% of students were found in the category of incomplete and 37% of students in the category of complete. Because the classical completeness of students is still relatively low, it is necessary to go to cycle 2. In cycle 2, it was found that 13% of students were in the unfinished category and 87% of students were in the completed category. This finding shows that there was an increase from cycle 1 to cycle 2. Thus, the researcher just stopped the cycle until cycle 2. This finding shows that the use of plastic ball modifications in learning can improve students' lower serve skills in volleyball games at SD Negeri Inpres Pasir 2. This is because plastic balls provide opportunities for students to more easily master the basic techniques of lower serves, so they can serve more accurately and consistently.